Efforts to Prevent COVID-19 in Penyak Village: Implementation of KKN-Thematic during the COVID-19 Pandemic - Fitri Afriani (Fakultas Kewirausahaan Universitas Garut, 2020)
COVID-19 pandemic is a global problem that affects various sectors of life and the Republic of Indonesia's Government has implemented a New Habit Adaptation program. Penyak Village is one of the villages in the Bangka Belitung Islands Province, where most people work as fishermen and farmers. It causes the majority of the community to work from outside the home. One of the activity programs of Universitas Bangka Belitung in response to COVID-19 is the implementation of KKN-Thematic to focus on efforts to prevent COVID-19. For Penyak Village, the KKN-Thematic program is carried out in several stages such as (i) preparation, (ii) preparing equipment to be given to the community, (iii) making video tutorials for making hand-sanitizers and masks, (iv) distributing health protocol equipment and counseling, and (v) evaluation. From the results, most community and village officials respond well to the activities that have been carried out.